PENATAAN MEKANISME PENYELESAIAN SENGKETA DUALISME KEPENGURUSAN INTERNAL PARTAI POLITIK DALAM SISTEM HUKUM INDONESIA DIKAITKAN DENGAN ASAS KEPASTIAN HUKUM - Pakpahan, Recksy H.; Indra, Mexsasai; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
A political party as an organization's political base has important roles in the democratic system and determines the direction of the passage of a state. In other words, political parties act as a regulator or managing conflict (conflict management), the party serves as a means interest aggregation (aggregation of interest) which distribute variety of different interests through institutional channels of party politics. However, it is not uncommon in the diversity it has given issues to inter-party or even just an internal party elite in the party itself. Problems between the party elite in the party's internal impact on the presence of two or more groups, and ultimately led to the dualism management.In the event of a dispute in the party court internal party as a mandate of Law No. 2 of 2011 jo Law No. 2 of 2008 on Political Parties should be able to perform its role as a cutter conflict like that contained in Article 32 paragraph (5) Law Act No. 2 of 2011. Countries should be able create the party court as an party institution of free and independent in carrying out the task to examine and decide the party's internal disputes. Excluding the settlement by the party court, the legislation also mandates the party conflict resolution mechanisms through the courts. However, in order to create the internal party mechanisms to resolve disputes through the court quickly and which do not overlap the decision that ultimately disrupt the principle of legal certainty required large-scale court reform that ultimately deemed the chaotic situation the party dispute on only one court roof. On the other side also needs to do a judicial review of Law No. 2 of 2011 on Political Parties. In the bill's new later was necessary to have clear regulations about how far the government can intervene in a political party, and most importantly set out clearly how the government through the Ministry of Justice and Human Rights (Kemenhumham) can issue a decree Management of a party as a legitimate leadership legitimacy.The purpose of this thesis are: First, to determine the mechanism of settlement of internal dualism in the management of Political Parties according to Law No. 2 of 2011 on Political Parties. Secondly, to determine the ideal arrangement on settlement mechanism in the management of the internal duality of Political Parties.This research is a normative legal research or can be also called as the doctrinal legal research. From the research there two subject matter concluded, first, .dualism settlement stewardship dispute in internal political party Law No.2 of 2011 jo, Law No. 2 of 2008 on "Political Party" still very ineffective and impressed bore overlapping decision. The Supreme Party or other designations in internal political party based Law No. 2 of 2011 had an important role to solve any political party's internal conflicts to this day has not been fully resolving problems in the internal party especially at the party's internal management. Secondly, there is no clear legal arrangement regarding the dispute resolution dualism in the management of internal political party through the court (litigation), resulting in problem solving could involve several judicial bodies. On the other hand the management attestation by the Decree of the Ministry of Law and Human Rights (SK Kemenhumham) is often a tool of the government to intervene against the political parties that increasingly worsen the problems in the party's internal politics. So it is necessary rearrangement of legal regulations in terms of dispute settlement in the internal management of the dualism of political parties.Keywords: Setting Period-Notice of Commencement of Investigation-Quick Principles-The Criminal Justice System